Effects of religious diversity on the employees' perception and reaction - Messarra, Leila (2010)
With increased globalization and emigration, religious diversity is becoming an essential part of workforce diversity. Drawing from the Lebanese experience, the aim of this paper is to highlight some concerns that might affect religiously diverse organizations around the world. Surveys were administered to 349 employees working in medium size religiously diverse organizations to determine their perceptions of religious discrimination in their organizations. Descriptive statistics, hypothesis testing, chi square and regression analysis found a positive relation between education and the perception of religious discrimination in the workplace. In addition, positive measures taken by the companies when dealing with religious diversity issues positively influences employees’ perception and reaction.